Variation of Sago Flour and Tapioca Starch in Carrot (Daucus carota L.) Fortified Mackerel (Scomberomorus commersonii) Sausages: Fortifikasi Pasta Wortel (Daucus carota L.) Pada Pembuatan Sosis Ikan Tenggiri (Scomberomorus commersonii) Dengan Variasi Tepung Sagu dan Tepung Tapioka - Andini, Monika; Nuraini, Vivi; Karyantina, Merkuria (JITIPARI, 2024)
Sausage is one of frozen food product that’s popular among the society. Mackerel is classified as a fish that’s low fat and higher in protein, and also has characteristics like white meat, thick and didn’t had contain many thorns, so it’s suitable for used in the processed of fish sausage. Innovation of fish sausage can be carried out by fortification provitamin A from carrot paste, and produced gluten-free mackerel sausage product by using sago flour and tapioca starch as a binder. The purpose of this study was to identify  characteristics of mackerel sausage fortified of carrot paste which is high in protein and β-carotene. The experimental design used is a Completely Randomized Design (CRD) with the first factor being the ratio of mackerel and carrot paste 75% : 25%, 50% : 50%, 25% : 75%. The second factor was the ratio of sago flour and tapioca starch as filler of sausage 80% : 20%, 60% : 40%, and 40%: 60%. The analysis indicated that the formulation of mackerel sausage which is highs in protein and the most preferred by consumers is found in the ratio of 75% mackerel : 25% carrot paste and 80% sago flour : 20% tapioca starch with a protein content of 11,36% and an overall level of preference is 3,55 (neutal). The mackerel sausage formulation that’s highs in β-carotene is found in the ratio of 25% mackerel: 75% carrot paste and 60% sago flour: 40% tapioca starch by 876 µg/g. Fortified carrot paste in mackerel sausages could be a  potensial source of protein and β-carotene.